Improving students' scientific literacy through inquiry learning at Solo Safari - Yuhanna, Wachidatul Linda; Retno, Raras Setyo (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
The scientific literacy of students in the animal diversity course has not met the criteria. Students are less concerned, passive, and do not dare to express their problem-solving comprehensively. The animal diversity course requires learning methods and learning resources to improve scientific literacy. The purpose of this study was to analyze the effect of inquiry learning on improving students' scientific literacy at Solo Safari. This research method is quantitative research with a quasi-experimental method. The research design uses pre and post-test results of students’ scientific literacy. The study population was 71 biology education students. The sample was 13 students who took the Animal Diversity course. The data taken is students' scientific literacy. The independent variable is inquiry learning at Solo Safari. The dependent variable is science literacy. The instrument used is a science literacy instrument, resulting in 15 valid statement items. Data analysis techniques were carried out with a paired sample t-test. N-gain score analysis was conducted to determine the effectiveness of science literacy. The results showed that the sig-value (2-tailed) = 0.000. The inquiry learning model affects students' scientific literacy. The inquiry learning model can improve students' scientific literacy. The result of the N-gain score on science literacy is 0.62 with moderate criteria. There is a significant increase in understanding of science literacy after students take part in learning with the inquiry approach. The conclusion of this study is, inquiry affects improving students' scientific literacy at Solo Safari. The application of inquiry in Solo Safari can increase students' scientific literacy in the moderate category. The implications of this study can be used as basic research to choose the right learning model for animal diversity courses. Science literacy instruments can also be used for various biological studies and other materials.